Clinical Effectiveness of Single Lumbar Periradicular Infiltration in Patients with Sciatica - Veljanovski, Dimitar; Kostova, Masha; Dejanova panev, Sandra; Ristikj-Stomnaroska, Daniela; Tatjana Deleva Stoshevska; Janevski, Petar; Bundovska Kocev, Smiljana; Prgova, Biljana (Macedonian Academy of Sciences and Arts/Walter de Gruyter GmbH, 2023)
Periradicular therapy (PRT) is a minimally invasive radiological procedurein patients with chronic lumbar pain.The aim of the study is to identify clinical and radiological predictive factors for treatment success after a single PRT treatment in patients with sciatica.The study includes a prospective follow-up of 166 patients treated with PRT. The pain intensity is determined according to the VAS scale and the degree of improvement is presented as excellent (over 75%), good (50-70%), moderate (25-49%), and weak (less than 25%). The follow up of the treated patients was done at 2 weeks, 3 and 6 months. In patients with pain duration up to 3 months, the improvement was excellent in n=32 (58.18%) after 2 weeks, after 3 months n=41 (74.55%) and after 6 months n=41 (74.55%). This stands in contrast to patients with pain over 1 year. The percentage of improvement after 6 months, post-intervention, was highest in patients without nerve root compression (86.25±19.2),and the highest improvement after 6 months was in patients with localization of pain at the L4-L5 level (69.69±29.7), the greatest improvement after six months was in patients with extraforaminal hernia (62.82±34.3), and the lowest in patients with central stenosis (40.21±30.7).Our study results suggest that the shorter a pain duration, low-grade root compression, injection level and type of herniation area predictor the more favourable response patients have to transforaminal epidural steroid injection in patients with sciatica.
Keywords: MRI; epidural; pain; radiculopathy; steroid